Composite Graft for Oblique Fingertip Amputation of the Ring Finger in an Adult: A Case Report and Literature Review - Zagat Indrawana; Nyoman Siska Ananda (Universitas Pendidikan Ganesha, 2026)
Fingertip amputations are common hand injuries that may significantly affect function and cosmetic appearance. Composite grafting is a relatively simple reconstructive technique that reattaches the amputated tissue without microvascular anastomosis and may provide satisfactory outcomes in selected adult patients. A 41-year-old male presented with a lateral oblique fingertip amputation of the right ring finger after a wood-cutting injury. Clinical examination revealed a 2.5 × 1.5 cm wound with exposed distal phalanx and non-viable tissue. The patient underwent debridement and composite grafting using the amputated fragment after trimming and thinning of excess subcutaneous tissue. Postoperative management included hand elevation, oral antibiotics, analgesics, and regular follow-up evaluations. Progressive graft maturation and satisfactory healing were observed, with satisfactory graft viability, preserved fingertip contour, and acceptable functional and cosmetic outcomes at one-month follow-up. Composite grafting remains a practical and cost-effective option for selected adult fingertip amputations, particularly when meticulous debridement, graft preparation, and postoperative care are performed. This case demonstrates favorable graft survival and satisfactory clinical outcomes following composite graft reconstruction in an adult patient.